1999
DOI: 10.1046/j.1469-8137.1999.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

A Lycopersicon esculentum phosphate transporter (LePT1) involved in phosphorus uptake from a vesicular–arbuscular mycorrhizal fungus

Abstract: In vesicular-arbuscular mycorrhizal symbioses, specialized fungal structures (the arbuscules) are formed which are in intimate contact with plant root cortical cells. It is assumed that these arbuscules are the major sites of solute transfer between the plant and fungus, but there have been no studies that definitively show the extent or types of transfer processes that occur in this structure. Phosphate is one of the major nutrients that is acquired by mycorrhizal fungi and transferred to plants. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 32 publications
5
36
0
9
Order By: Relevance
“…Arbuscules has been acclaimed as the major site for the exchange of minerals (in particular phosphorus) and carbohydrates between both partners in the AM symbiosis (Rosewarne et al, 1999;Rausch et al, 2001). Using a similar in vitro autotrophic cultivation system, Dupré de Boulois et al (2006) demonstrated the transport of P from a hyphal compartment to a root compartment and subsequently to the plant shoot cells via the fungal interface, while the transport of carbohydrates from plant to the AM fungus was investigated by Voets et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscules has been acclaimed as the major site for the exchange of minerals (in particular phosphorus) and carbohydrates between both partners in the AM symbiosis (Rosewarne et al, 1999;Rausch et al, 2001). Using a similar in vitro autotrophic cultivation system, Dupré de Boulois et al (2006) demonstrated the transport of P from a hyphal compartment to a root compartment and subsequently to the plant shoot cells via the fungal interface, while the transport of carbohydrates from plant to the AM fungus was investigated by Voets et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…A high-affinity phosphate transporter from Glomus seems to be responsible for the uptake of phosphate by hyphae growing in the soil [44]. The Lycopersicon esculentum PHOSPHATE TRANSPORTER1 (LePT1)-encoded transporter from tomato also appears to be involved in symbiotic phosphate translocation, as indicated by the high levels of LePT1 transcripts that were detected by in situ hybridization in arbusculated cells [45]. The site of carbohydrate translocation towards AM fungi is unclear.…”
Section: Transport Phenomena At Biotrophic Interfacesmentioning
confidence: 99%
“…Supporting evidence includes: i) ATP-hydrolyzing activity, possibly P-ATPase, was localized on periarbuscular membrane of the host (Gianinazzi-Pearson et al, 1991) and ii) High-affinity Pi transporters (Rosewarne et al, 1999;Rausch et al, 2001) and P-ATPase (Gianinazzi-Pearson et al, 2000) genes are expressed in arbuscule-containing host cells.These observations suggest that Pi is actively taken up by the plant through the periarbuscular membrane. iii) ATP-hydrolyzing activity on the fungal plasma membrane of arbuscules is absent (Gianinazzi-Pearson et al, 1991) and iv) the fungal P transporter gene GvPT is not expressed within the roots (Harrison and Van Buuren, 1995).…”
Section: Regulation Of Pi Transfer Via Arbusculesmentioning
confidence: 99%